# How do you solve #(x-1) /3 - (x-1)/2 = 6#?

##### 1 Answer

Oct 16, 2016

#### Answer:

#### Explanation:

Start by making sure that you're working with fractions that have **equal denominators**.

You start with

#(x-1)/3 - (x-1)/2 = 6/1#

The *common denominator* here is

This will get you

#(x-1)/3 * 2/2 - (x-1)/2 * 3/3 = 6/1 * 6/6#

#(2(x-1))/6 - (3(x-1))/6 = 36/6#

At this point, drop the denominators and focus exclusively on the numerators.

#2(x-1) - 3(x-1) = 36#

This will get you

#-(x-1) = 36#

#-x + 1 = 36#

#x = - 35#

Do a quick check to make sure that the calculations are correct

#(-35 - 1)/3 - (-35 - 1)/2 = 6#

#-36/3 + 36/2 = 6#

#-12 + 18 = 6 " "color(green)(sqrt())#